Growth rate of Acropora formosa coral fragments transplanted on different composition of faba kerbstone artificial reef - ruly isfatul khasanah; ENDANG YULI HERAWATI; ANIK MARTINAH HARIATI; MOHAMMAD MAHMUDI; AIDA SARTIMBUL; DEWA GEDE RAKA WIADNYA; EVRON ASRIAL; YUDATOMO; ERRY NABIL (Society for Indonesian Biodiversity, 2019)
Abstract. Khasanah RI, Herawati EY, Hariati AM, Mahmudi M, Sartimbul A, Wiadnya DGR, Asrial E, Yudatomo, Nabil R. 2019. Growth rate of Acropora formosa coral fragments transplanted on different compositions of faba kerbstone artificial reef. Biodiversitas 20: 3593-3598. A counter measure and an alternative technique to reduce coral reef destruction is through transplantation, which requires the relocation or cutting of a live coral, planted in a designated place containing damaged varieties. Faba kerbstone is a product innovation similar to paving block/brick, made from fly and bottom ash (FABA), which is the dominant waste product from PT Jawa Power, Probolinggo, Indonesia. In addition, it has also been widely utilized as a raw material in the creation of paving and concrete blocks, composed by harmless material, with a length, width, and height of 40, 25 and 15 cm, respectively. This study aims to observe the growth rate of Acropora formosa coral fragments transplanted on a faba kerbstone, using five different fly and bottom ash compositions: K1 = 0% Fa, K2 = 25% Fa and 75% Ba, K3 = 50% FA and 50% Ba, K4 = 75% Fa and 25% Ba, while K5 = 100% Fa and 0% Ba. Furthermore, the observations were conducted underwater, using scuba diving for six months, observing the parameters of fragment length, colony diameter, and branches number. In addition, the highest elongation rate of A. formosa coral fragments was identified at K2 (1.313 ± 0.447 cm/month), and K1 (1.185 ± 0.642 cm/month), while the most significant increment in colony diameter was observed in K2 (0.077 ± 0.060 cm/month) and K1 (0.063 ± 0.071 cm/month), and the largest number of branches was also found in K2 (29.50 or 4.28 branches/month) and K1 (25.25 or 3.67 branches/month). Furthermore, the one-way ANOVA and Tukey's HSD test (p = 0.05) showed was no significant difference in the fragments elongation and colony diameters in the K1 and K2 models, although there was substantial variation from the K3, K4, and K5.